Molecular Insights into the Diversification and Biogeographic History of Six Astragalus L. Sections in the Turkish Flora - Mevlüde Alev Ateş; Seher Karaman; Zeki Aytaç; Zeki Kaya (Plants, 2025)
With 493 taxa and 63 sections, Astragalus L. is the largest genus in Türkiye. Most of these are narrow endemics and usually found in marginal habitats or require edaphic specializations (about 42% of the species are endemic). Due to the genus’s extensive diversity of species and common economic use, numerous scientific studies have concentrated on specific species. Taxonomic categorization based on morphological characteristics is insufficient to distinguish certain taxonomic groups. However, there is no systematic molecular phylogenetic analysis of Turkish species that deals with speciation in this genus. To concentrate on molecular-level speciation, fresh leaves from 152 samples representing 30 species across six sections native to Türkiye were collected over several months of comprehensive field studies and analyzed with regard to the internal transcribed spacer (ITS) of nrDNA and the trn L5′-L3′ + L3′-F(GAA) + mat K of cpDNA regions. Additionally, molecular clock estimations and biogeographical histories were analyzed to clearly understand the species’ divergence. Based on all studied regions, the Poterion section was found to be the newest and most divergent section, while the Megalocystis Bunge and Halicacabus Bunge sections were the closest and older ones. Furthermore, A. vaginans from section Hymenocoleus Bunge were included not only in this section but also in several other lineages. It is noteworthy that A. dipodurus and A. oleaefolius species from the section Macrophyllium Bunge are usually put together in a distinct sub-branch from other species members of the section in phylogenetic trees generated using both researched cpDNA and nrDNA regions. Moreover, some of the species are divided by the Anatolian diagonal, and the speciation of a significant number of species began during the Pleistocene geological time period. Geographical isolations or other weak isolation mechanisms preceded speciation in Astragalus, which requires more research in the future.